A statistical Study of the effect of using networking sites on Academic Achievement - سلمان معلا (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to study an analytical study on the experimental study of social learning on the experimental study, University of Hama, by applying it to a random sample of students from the Faculty of Education, after distributing a questionnaire consisting of 22 variables to 400 male and female students from the Faculty of Education at the University of Hama, and then emptying The questionnaire using statistical and experimental research methods. Among the results obtained: - The science of studying social networking sites on the degree of academic achievement for university students. - Social communication, sociability, information about ascension, and information in society. - Social networking sites have provided ample space for university students to increase their scientific and academic achievement, in addition to the ease of searching for the scientific references they want. Social networking sites contribute to life skills and intellectual values, and educate university students about the events around them.